2020
DOI: 10.1007/978-3-030-40186-3_24
|View full text |Cite
|
Sign up to set email alerts
|

Traceable Inner Product Functional Encryption

Abstract: Functional Encryption (FE) has been widely studied in the last decade, as it provides a very useful tool for restricted access to sensitive data: from a ciphertext, it allows specific users to learn a function of the underlying plaintext. In practice, many users may be interested in the same function on the data, say the mean value of the inputs, for example. The conventional definition of FE associates each function to a secret decryption functional key and therefore all the users get the same secret key for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The functional decryption key will not only be specific to a function but to a user too, in such a way that if some users collude to produce a pirate decoder that successfully evaluates a function on the plaintext, from the ciphertext only, one can trace back at least one of them. In [81], Do et al propose a traceable IP-FE with black-box confirmation, using the pairing. 8.9.…”
Section: Other Fe Schemesmentioning
confidence: 99%
See 1 more Smart Citation
“…The functional decryption key will not only be specific to a function but to a user too, in such a way that if some users collude to produce a pirate decoder that successfully evaluates a function on the plaintext, from the ciphertext only, one can trace back at least one of them. In [81], Do et al propose a traceable IP-FE with black-box confirmation, using the pairing. 8.9.…”
Section: Other Fe Schemesmentioning
confidence: 99%
“…Adding traitor tracing to public-key encryption indeed requires a very high extra cost: even in the bounded model, the cost grows proportionally with the number of traitors. In [78], a new primitive, called Traceable Functional Encryption, is defined: the functional decryption key will not only be specific to a function, but to a user too, in such a way that if some users collude to produce a pirate decoder that successfully evaluates a function on the plaintext, from the ciphertext only, one can trace back at least one of them. In [78], Do et al propose a traceable IP-FE with black-box confirmation, using the pairing.…”
Section: Multi-input Fe Multi-input Functional Encryption (Mi-fementioning
confidence: 99%
“…Boneh and Franklin [46] introduced the first algebraic traitor tracing scheme, which is also the basis of many follow-up works, including public-key based schemes [47][48][49][50][51][52][53][54][55], identity-based schemes [56][57][58][59][60], and attribute-based schemes [52,54,[61][62][63][64]. In particular, Do et al [65] recently introduced the concept called traceable inner product function encryption, which gives the generalization of the identity-based and attribute-based traitor tracing schemes to support more flexible policies.…”
Section: Traitor Tracingmentioning
confidence: 99%
“…In particular, Do et al. [65] recently introduced the concept called traceable inner product function encryption, which gives the generalization of the identity‐based and attribute‐based traitor tracing schemes to support more flexible policies.…”
Section: Related Workmentioning
confidence: 99%
“…The tracing problem becomes critical for this situation. In [33], a new primitive, called Traceable Functional Encryption (TFE), was defined in order to deal with multi-user setting and traceability. By exploiting the similarities between the Boneh and Franklin's traitor tracing scheme [15] and the Abdalla et al's IPFE scheme [6], it was shown how to integrate the Boneh-Franklin tracing technique into the IPFE scheme of Abdalla et al, which allows in particular the personalization of functional decryption keys.…”
Section: Functional Encryption: Moving From Revealing All-or-nothing To Partial Informationmentioning
confidence: 99%